Sulfur-containing palladacycles as catalyst precursors for the heck reaction - Gruber, Adriane S. [UNESP]; Zim, Danilo; Ebeling, GUnter; Monteiro, Adriano L.; Dupont, Jaïrton (American Chemical Society (ACS), 2000)
(formula presented) The air, water, and highly thermally stable sulfur-containing palladacycles, mainly derived from the ortho-palladation of benzylic thioethers, are exceptional catalyst precursors for the Heck reaction. The reaction can be performed with aryl iodides, bromides, and chlorides, with acrylic esters and styrene, leading to turnover numbers up to 1 850 000.